2003
DOI: 10.1002/pd.597
|View full text |Cite
|
Sign up to set email alerts
|

Centre‐specific ultrasound nuchal translucency medians needed for Down syndrome screening

Abstract: Nuchal translucency (NT) measurements were compared between 13 centres participating in a multi-marker Down syndrome screening program. Results from 4765 women were analysed, and there were highly statistically significant between-centre differences after allowing for gestation (P < 0.0001). Examination of maternal serum marker levels, expressed in multiples of the median (MoM) for gestation, showed that this was not due to gestational errors. Regression analysis was carried out to derive an equation with a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 22 publications
1
22
0
Order By: Relevance
“…Additionally, calculation of multiples of the median (MoM) values provides a useful parameter that can be used to assess variation between operators. The median NT‐MoM value should be 1.0 if the NT measurements of a single operator or group of operators do not deviate from the modeled median reference curve13–16. To ensure good quality NT measurements, the accepted median NT‐MoM of an operator should be limited, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, calculation of multiples of the median (MoM) values provides a useful parameter that can be used to assess variation between operators. The median NT‐MoM value should be 1.0 if the NT measurements of a single operator or group of operators do not deviate from the modeled median reference curve13–16. To ensure good quality NT measurements, the accepted median NT‐MoM of an operator should be limited, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Despite adhering to their guidelines markedly different medians were determined. One approach suggested to correct for differences in median between individuals and centers is the use of center or operator specific medians [15,22]. Such an approach, however, would only be possible for sonographers and centers which performed frequent combined first-trimester NT assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, all sonographers assessed performed scans at one single Institution and thus variation in clinical practice between Institutions could not be assessed. Variation between centers has been reported in several studies [7,15]. Secondly, we have adopted an epidemiological approach to the monitoring of NT measurement quality assurance and did not perform a qualitative assessment of images using criteria reported in other studies [7,[24][25][26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some have suggested that there either be individual or at least center‐specific NT medians used to compensate for the variation seen (Logghe et al , 2003; Malone et al , 2005; Palomaki et al , 2009; Wapner et al , 2003). Unfortunately, we have shown decreased performance in such circumstances, and then there is no incentive to improve performance (Evans et al , 2007b).…”
Section: Discussionmentioning
confidence: 99%